2018
DOI: 10.1186/s13287-018-0772-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: hPMSC transplantation restoring ovarian function in premature ovarian failure mice is associated with change of Th17/Tc17 and Th17/Treg cell ratios through the PI3K/Akt signal pathway

Abstract: BackgroundHuman placenta-derived mesenchymal stem cell (hPMSC) transplantation has been demonstrated to be an effective way of recovering ovarian function in mice with autoimmune induced premature ovarian failure (POF). But the exact mechanism remains unclear. The goal of the present study is to investigate the role of immune factors (T-helper 17 (Th17), cytotoxic T (Tc17) and regulatory T (Treg) cells) in the recovery of ovarian function and whether the phosphatidylinositol 3-kinase (PI3K)/Akt signal pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 43 publications
3
51
0
Order By: Relevance
“…FSHR, which can serve as a marker of GCs, is positive in almost all of the cells' cytoplasm ( Fig. 1f), in accordance with our previous reports [3].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…FSHR, which can serve as a marker of GCs, is positive in almost all of the cells' cytoplasm ( Fig. 1f), in accordance with our previous reports [3].…”
Section: Resultssupporting
confidence: 92%
“…The ovarian histological changes were observed by light microscopy (Olympus). We counted the follicles containing obvious nucleus in the experiment, which were divided into primordial, primary, secondary, antral, and atretic follicles, which were described before [3,34].…”
Section: Follicle Counting and Ovarian Morphological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…showed that PD-MSCs have therapeutic bene ts in mice with premature ovarian failure because they regulate regulatory T-cell activity and cytokines [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Because of these immunosuppressive properties, there are ongoing clinical trials with PD-MSCs in several disease types including certain autoimmune diseases [15][16][17]. Recently, Yin N et al, showed that PD-MSCs have therapeutic bene ts in mice induced with premature ovarian failure by regulating regulatory Tcell activity and cytokines [18,19].…”
Section: Introductionmentioning
confidence: 99%